2001
DOI: 10.1161/hs1001.097222
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Stroke in Australia From a Societal Perspective

Abstract: Background and Purpose-Accurate information about resource use and costs of stroke is necessary for informed health service planning. The purpose of this study was to determine the patterns of resource use among stroke patients and to estimate the total costs (direct service use and indirect production losses) of stroke (excluding SAH) in Australia for 1997. Methods-An incidence-based cost-of-illness model was developed, incorporating data obtained from the North EastMelbourne Stroke Incidence Study (NEMESIS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(68 citation statements)
references
References 31 publications
5
61
1
1
Order By: Relevance
“…Other important categories were rehabilitation costs (16%), readmission costs (11%) and medication costs (9%). Australia: The direct lifetime costs following a first-ever stroke were also found to be twice those of the first-year costs of stroke in Australia, based on an incidence-based cost-of-illness model (16). In this study, the major drivers of the costs of stroke during the first year were acute hospitalization (28%), followed by inpatient rehabilitation (27%) and nursing home care (11%).…”
Section: Strokementioning
confidence: 63%
See 2 more Smart Citations
“…Other important categories were rehabilitation costs (16%), readmission costs (11%) and medication costs (9%). Australia: The direct lifetime costs following a first-ever stroke were also found to be twice those of the first-year costs of stroke in Australia, based on an incidence-based cost-of-illness model (16). In this study, the major drivers of the costs of stroke during the first year were acute hospitalization (28%), followed by inpatient rehabilitation (27%) and nursing home care (11%).…”
Section: Strokementioning
confidence: 63%
“…Ten studies estimating the cost of stroke (12,(15)(16)(17)(18)(19)(20)(21)(22)(23), of which three were Canadian studies and two were European reviews, were identified and are summarized in Table 2. Canada: Based on various public and private sources, the direct cost of stroke in Ontario was calculated to be at 2.7% of the total direct health care expenditures of Ontario (15).…”
Section: Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Indirect costs vary substantially between studies mainly because of differences in the mode of calculation. For example, it was estimated that indirect costs constituted 58 percent of total lifetime cost per person in the United States (27), 22 percent to 24 percent of the annual costs of stroke in the Netherlands and Sweden (8;28), and 6 percent of the first-year cost per patient in Australia (7).…”
mentioning
confidence: 99%
“…2 It is a predictor of poorer outcome and need for residential care 3 , increased length of hospital stay 3 and 1-year and lifetime costs. 4 High-intensity dysphagia therapy yields favourable outcomes in acute stroke patients, with significantly fewer patients needing modified diets, dying or requiring residential care by 6 months post stroke. 5 Aims/Hypotheses: We sought to determine dysphagia incidence, prevalence at 7 days and dysphagia management practices of Speech Pathologists in Australian stroke units.…”
Section: Methodsmentioning
confidence: 99%